Strength and sorption properties of plastic composites made from eremospatha macrocarpa and laccosperma secundiflorum canes (2011)
"The dwindling timber resource and the attendant shortage of wood supply call for alternative furnish for composite production. Rattan canes are candidate materials due to their availability, renewability and inexpensive processing cost. This work therefore examined the feasibility of using rattan canes as reinforcements for plastic composites production by evaluation the strength and sorption properties. Particles extracted from Eremosphatha macrocarpa and Laccosperma secundiflorum canes harvested from wild stocks were milled into 0.4mm, dried to 0.5% moisture content, blended with high density polythylene (HDPE), talcum, zinc stearate Ethylene bistearamide (EBS) wax in the ratio 1.0:0.82: 0.12:0.04:0.02 respectively and extruded using rotating twin-screw at barrel and die temperatures of between 149 and 193 oC. The composite were cut to sample sizes and tested for flexural properties on a universal testing machine while sorption properties were evaluated after 2 and 24 hours immersion in water. The results obtained revealed that the respective moduli of ruputre and elsaticities of the E. macrocarpa and L. secundiflorum composites were 26.2 and 26.4 N/mm2 and 2689 and 3406 N/mm2 while the water absorption were between 1.2 to 3.1% and 1.0 to 2.4% and thickness swelling were 0.4 to 1.0 and 0.3 and 0.9% after 2 and 24 hours immersion in water. The study revealed that rattan canes were suitable as reinforcement for plastic composite production, dimensionally stable with low water absorption and thickness swelling rates and can be applied for both structural and non-structural interior and exterior purposes. Differences in the rattan anatomy influenced the ductility and sorption properties of the plastic composites "